DEVELOPMENT OF THE CONTROL SYSTEM REGARDING THE SPREAD OF INFECTIOUS DISEASES IN THE RUSSIAN EMPIRE BE-FORE THE TWENTIETH CENTURY - Anatolii Hrynzovskyi (Bogomolets National Medical University, 2020)
None of the areas of medicine has so far managed to save as many lives as epidemiology, namely immunoprophylaxis. The history of immunoprophylaxis dates back many centuries, but as a specialized scientific and medical field dates back to May 14, 1796. It was on this day that the English physician Edward Anthony Jenner began to practice vaccinations against smallpox.